IMPLEMENTATION DESIGN OF CURRICULUM 2013 IN THE THEMATIC LEARNING PROCESS IN INTEGRATED ISLAMIC ELEMENTARY SCHOOL - Zaenuri Zaenuri; Mohamad Agung Rokhimawan (JIP Jurnal Ilmiah PGMI, 2022)
In the 2013 curriculum, thematic learners are no longer teacher-centred but rather on students, learning is no longer one-way but more participatory because it is more student-centered. The focus of this research is to look at the implementation of thematic learning at SDIT Bina Ilmi Palembang. This research applies qualitative methods, namely taking descriptive approaches and field observations, as well as studying relevant books. Data retrieval techniques use observation and interview guidance instruments while data analysis techniques use Miles and Huberman's interactive analysis models, which include data reduction, data presentation, and conclusion drawing. The results showed that SDIT Bina Ilmi Palembang in the implementation of thematic learning of teacher using thematic guidebooks and packaging materials as best as possible by making learning media so that students could achieve affective, cognitive, and psychomotor aspects. The methods of implementation of the learning process used in thematic learning vary so that students do not get bored such as, role playing, Q&A, singing, assigning tasks, group discussions, observations, and exercises then also apply integrated methods, namely, study, exploration, formulate, present, apply (worldly and ukhrowi) in which students can play an active role and also other goals so that students do not only master the cognitive realm but its affective and psychomotor are constantly evolving.